Public Policy Design via Composite Indicators of Economic Development and Labor Absorption - Muammil Sun'an; Nurul Hidayah; Nahu Daud (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2026)
This study investigates the impact of regional economic development on labor absorption in North Maluku Province. To address the challenge of multicollinearity among development indicators, it proposes the use of a composite Economic Development Index (EDI). The EDI was constructed using Principal Component Analysis (PCA) based on four key indicators: Gross Regional Domestic Product (GRDP), minimum wage, urbanization rate, and investment. The first principal component (PC1), explaining 85.9% of the variance, was used as a unified predictor in a linear regression model to assess its relationship with labor absorption. Data were sourced from official statistics spanning 2013 to 2024. The PCA successfully condensed the multivariate dataset into a robust single index. Regression analysis using PC1 revealed a strong, positive, and statistically significant association with labor absorption, with an R-squared value of 0.833. This indicates that 83.3% of the variation in employment levels in North Maluku is explained by changes in the EDI. Findings emphasize the effectiveness of PCA in regional labor market studies and suggest that integrated improvements across GRDP, wages, urbanization, and investment substantially enhance employment. This methodological approach offers a replicable framework for policymakers aiming to design targeted and balanced regional development strategies.